ASOCIACIÓN Y CAPACIDAD PREDICTIVA DE LA PROTEINURIA DE 24 HORAS EN COMPLICACIONES MATERNAS Y PERINATALES DE GESTANTES CON PREECLAMPSIA - Oblitas Cupén, Sofía (2026)
Introduction. Proteinuria may be associated with increased maternal and perinatal morbidity and mortality. Objectives.To evaluate the association of 24-hour proteinuria with maternal and perinatal complications and its predictive ability.Methods. A retrospective cohort study was conducted at Hospital Regional José Cayetano Heredia, Piura, from 2022to 2024. A total of 249 pregnant women with preeclampsia who underwent 24-hour urine protein measurement wereincluded. Proteinuria was stratified as normal <300 mg/24 h, mild 300–1000 mg/24 h, moderate 1001–3000 mg/24 h,and severe ≥3001 mg/24 h. Maternal and perinatal complications were recorded. Crude and adjusted relative risks(aRR) with 95% confidence intervals (95% CIs) were estimated. Predictive performance was assessed using receiveroperating characteristic (ROC) curves and area under the curve (AUC). Results. Compared with normal proteinuria,severe proteinuria increased the risk of effusion (aRR = 22.42; 95% CI: 3.64–138.17), prematurity (aRR = 1.87;95% CI: 1.35–2.60), low birth weight (aRR = 1.86; 95% CI: 1.22–2.84), neonatal depression (aRR = 3.03; 95% CI:1.18–7.76), neonatal resuscitation (aRR = 3.54; 95% CI: 1.42–8.78), and admission to the neonatal intensive careunit (NICU) (aRR = 3.48; 95% CI: 1.71–7.10). Likewise, moderate proteinuria increased the risk of postpartum anemia(aRR = 1.36; 95% CI: 1.14–1.61) and NICU admission (aRR = 2.25; 95% CI: 1.11–4.60). Mild proteinuria reducedthe risk of emergency cesarean section (aRR = 0.82; 95% CI: 0.72–0.93). ROC curves showed AUC values between0.489 and 0.753, with the highest discrimination for effusion (AUC=0.753). Conclusion. Twenty-four-hour proteinuriawas associated with maternal and perinatal complications; however, its isolated predictive performance was limitedand should be interpreted within the clinical context.